Method for producing high-strength steel sheet

JP2025012219AActive Publication Date: 2025-01-24JFE STEEL CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023114914
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-13
Publication Date
2025-01-24
Estimated Expiration
2043-07-13

AI Technical Summary

Benefits of technology

【0007】 本発明によれば、熱延鋼板を冷間圧延する際の通板性に優れる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025012219000005
    Figure 2025012219000005
  • Figure 2025012219000001
    Figure 2025012219000001
  • Figure 2025012219000002
    Figure 2025012219000002
Patent Text Reader

Abstract

To provide a method for producing a high-strength steel sheet excellent in sheet passing property when cold rolling a hot-rolled steel sheet.SOLUTION: A hot-rolled steel sheet having by mass% C: 0.20-0.50%, Si: 0.5-2.5%, Mn: 2.5-5.0%, P: 0.100% or less, S: 0.0500% or less, Al: 0.01-0.50% and N: 0.010% or less is subjected to a softening treatment (Temperature: Ta-50-Ta+50°C, Duration: ta hour or less) and then cold-rolled to obtain a cold-rolled steel sheet. The cold-rolled steel sheet is heated at a temperature T1 in an austenite single-phase region for 15-1000 seconds, cooled to a temperature T2 of Ms-50°C or more and less than Ms°C, raised to a temperature T3 of 500°C or less and held for 15-1000 seconds, cooled to a temperature T4 of Ms-200°C or more and less than the temperature T2, raised to a temperature T5 of 500°C or less and held for 15-1000 seconds. Ta=600-[Si%]×100 ta=10-[Si%]×4SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a high strength steel plate. [Background technology]

[0002] In recent years, from the viewpoint of protecting the global environment, improving the fuel efficiency of automobiles has become an important issue. For this reason, there has been active movement to reduce the weight of the car body itself by increasing the strength of car body materials such as steel plates to make the car body parts thinner.

[0003] Patent Document 1 discloses a method for producing high-strength steel plate, in which a "cold-rolled steel plate" obtained by "hot rolling and then cold rolling a steel slab having a composition containing, by mass%, C: 0.20% to 0.50%, Si: 0.5% to 2.5%, Mn: 2.5% to 5.0%, P: 0.100% or less, S: 0.0500% or less, Al: 0.01% to 0.50%, and N: 0.010% or less, with the balance being Fe and unavoidable impurities" is subjected to a specific heat treatment ([Claim 1]). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent Publication No. 2021-123801 Summary of the Invention [Problem to be solved by the invention]

[0005] When a hot-rolled steel sheet obtained by hot rolling is cold-rolled, the sheet passability may be insufficient (the hot-rolled steel sheet may crack or break, or may be too hard to be rolled). Therefore, an object of the present invention is to provide a method for producing a high strength steel sheet which has excellent sheet passing properties when the hot rolled steel sheet is cold rolled. [Means for solving the problem]

[0006] As a result of intensive research, the present inventors have found that the above object can be achieved by adopting the following configuration, and have completed the present invention. That is, the present invention provides the following [1] to [3]. [1] A steel slab having a composition containing, by mass%, C: 0.20% to 0.50%, Si: 0.5% to 2.5%, Mn: 2.5% to 5.0%, P: 0.100% or less, S: 0.0500% or less, Al: 0.01% to 0.50%, and N: 0.010% or less, with the balance being Fe and unavoidable impurities, is hot-rolled to obtain a hot-rolled steel sheet, and the hot-rolled steel sheet is softened by heating at a treatment temperature Ta1 of Ta-50°C to Ta+50°C for a treatment time ta1 not exceeding ta; A method for producing a high strength steel plate, comprising cold rolling the hot rolled steel plate that has been subjected to the softening treatment to obtain a cold rolled steel plate, heating the cold rolled steel plate at a temperature T1 in the austenite single phase region for 15 seconds or more and 1000 seconds or less, subsequently cooling to a temperature T2 of Ms-50°C or more and less than Ms°C, subsequently heating to a temperature T3 of 500°C or less and holding this for 15 seconds or more and 1000 seconds or less, subsequently cooling to a temperature T4 of Ms-200°C or more and less than the above temperature T2, and subsequently heating to a temperature T5 of 500°C or less and holding this for 15 seconds or more and 1000 seconds or less. When the content of component X in the above-mentioned composition is expressed in units of mass % as [X%], Ta, ta and Ms are calculated by the following formula in units of ° C., time and ° C., respectively. Ta=600-[Si%]×100 ta=10-[Si%]×4 Ms=550-35×[Mn%]-13×[Si%]-10×[Cr%]-12×[Mo%]-600×{1-exp(-0.96×[C%])} [2] The method for producing a high-strength steel plate according to the above item [1], wherein the chemical composition further contains, by mass%, at least one selected from the group consisting of Ti: 0.100% or less, Nb: 0.100% or less, V: 0.100% or less, Ta: 0.100% or less, W: 0.500% or less, Cu: 2.00% or less, Ni: 1.00% or less, Sn: 0.200% or less, Sb: 0.200% or less, Cr: 1.000% or less, Mo: 1.000% or less, B: 0.0050% or less, Mg: 0.0050% or less, Zr: 0.100% or less, REM: 0.0050% or less, and Ca: 0.0050% or less. [3] The method for producing a high-strength steel sheet according to [1] or [2] above, wherein the hot-rolled steel sheet that has been subjected to the softening treatment has carbides having a diameter of 50 nm or less. Effect of the Invention

[0007] According to the present invention, the hot-rolled steel sheet has excellent sheet passing properties when being cold-rolled. [Brief description of the drawings]

[0008] [Figure 1] FIG. 2 is a schematic diagram showing a temperature pattern of a heat treatment after cold rolling. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] [Manufacturing method for high-strength steel plates] A method for producing a high-strength steel plate according to this embodiment (hereinafter also referred to as "this production method") will be described. In this manufacturing method, generally speaking, a steel slab having a specific component composition is first hot-rolled to obtain a hot-rolled steel sheet. The hot-rolled steel sheet is then subjected to a softening treatment, which will be described later, and then cold-rolled to obtain a cold-rolled steel sheet. The cold-rolled steel sheet is then subjected to a specific heat treatment. In this way, a high-strength steel sheet (a heat-treated cold-rolled steel sheet) is obtained. Hereinafter, the "high strength steel sheet" or the "cold rolled steel sheet" will also be simply referred to as the "steel sheet".

[0010] <Composition of Steel Billets> First, the chemical composition of the steel slab will be described. Unless otherwise specified, "%" in the composition of the components means "% by mass."

[0011] 《C: 0.20% or more and 0.50% or less》 C is an essential element for increasing the strength of steel sheets by ensuring the amount of tempered martensite and martensite in the steel sheets, and for increasing the amount of retained austenite in the steel sheets by ensuring the high ductility of the steel sheets. From the viewpoint of ensuring the strength and workability of the steel sheet, the C content is 0.20% or more, preferably 0.21% or more, and more preferably 0.22% or more. On the other hand, if the C content is too high, the steel sheet becomes embrittled, so the C content is 0.50% or less, preferably 0.40% or less, and more preferably 0.30% or less.

[0012] 《Si: 0.5% or more and 2.5% or less》 Silicon is a useful element that contributes to improving the strength of steel sheets through solid solution strengthening, and also contributes to ensuring the amount of retained austenite in steel sheets by suppressing the formation of carbides in the steel sheets. In order to obtain the effect of adding Si, the Si content is 0.5% or more, preferably 0.6% or more, and more preferably 0.7% or more. On the other hand, if the Si content is too high, the steel sheet becomes embrittled, so the Si content is 2.5% or less, preferably 2.2% or less, and more preferably 2.0% or less.

[0013] 《Mn:2.5% or more and 5.0% or less》 Mn is an element that stabilizes the retained austenite, is effective in ensuring good ductility, and further increases the strength of the steel by solid solution strengthening. In addition, Mn enrichment in the retained austenite ensures a large amount of retained austenite. From the viewpoint of obtaining such an effect of adding Mn, the Mn content is 2.5% or more, preferably 2.6% or more, and more preferably 2.8% or more. On the other hand, if Mn is added excessively, the workability deteriorates due to segregation of Mn, and therefore the Mn content is 5.0% or less, preferably 4.8% or less, and more preferably 4.5% or less.

[0014] 《P:0.100% or less》 P is an element useful for strengthening steel, but if the amount of P is too much, it embrittles due to grain boundary segregation, so the amount of P is 0.100% or less, preferably 0.050% or less, and more preferably 0.030% or less. On the other hand, excessive reduction in the P content leads to a significant increase in costs, so the P content is preferably 0.001% or more, and more preferably 0.003% or more.

[0015] 《S:0.0500% or less》 Since S becomes inclusions such as MnS and causes cracks when evaluating stretch flangeability, it is preferable to reduce the S content as much as possible. For this reason, the S content is 0.0500% or less, preferably 0.0300% or less, and more preferably 0.0100% or less. On the other hand, excessive reduction in the S content leads to a significant increase in costs, and therefore the S content is preferably 0.0003% or more, more preferably 0.0005% or more, and even more preferably 0.0008% or more.

[0016] 《Al: 0.01% or more and 0.50% or less》 Al is a useful element that is added as a deoxidizer in the steelmaking process. In order to obtain the effect of adding Al, the Al content is 0.01% or more, preferably 0.02% or more, and more preferably 0.03% or more. On the other hand, if the Al content is too high, the risk of slab cracking during continuous casting increases, so the Al content is 0.50% or less, preferably 0.40% or less, and more preferably 0.30% or less.

[0017] 《N:0.010% or less》 N is the element that most significantly deteriorates the aging resistance of steel, and it is preferable to reduce the N content as much as possible. Therefore, the N content is 0.010% or less, preferably 0.008% or less, and more preferably 0.007% or less. On the other hand, excessive reduction in the N content leads to a significant increase in costs, and therefore the N content is preferably 0.001% or more, more preferably 0.002% or more, and even more preferably 0.003% or more.

[0018] Other Ingredients The component composition may further contain, in mass %, at least one component selected from the group consisting of the components described below.

[0019] (Ti:0.100% or less) Ti is useful for precipitation strengthening of steel. However, if the Ti content is too high, the workability and shape fixability may become insufficient. Therefore, when Ti is contained, from the viewpoint of improving the workability, the Ti content is preferably 0.100% or less, more preferably 0.080% or less, and further preferably 0.060% or less. On the other hand, when Ti is contained, in order to obtain the effect of adding Ti, the Ti amount is preferably 0.005% or more, more preferably 0.008% or more, and further preferably 0.010% or more.

[0020] (Nb:0.100% or less) Nb is useful for precipitation strengthening of steel. However, if the Nb content is too high, the workability and shape fixability may become insufficient. Therefore, when Nb is contained, from the viewpoint of improving the workability, the Nb content is preferably 0.100% or less, more preferably 0.080% or less, and further preferably 0.060% or less. On the other hand, when Nb is contained, in order to obtain the effect of adding Nb, the Nb amount is preferably 0.005% or more, more preferably 0.008% or more, and further preferably 0.010% or more.

[0021] (V:0.100% or less) V is useful for precipitation strengthening of steel. However, if the V content is too high, the workability and shape fixability may become insufficient. Therefore, when V is contained, from the viewpoint of improving the workability, the V content is preferably 0.100% or less, more preferably 0.080% or less, and further preferably 0.060% or less. On the other hand, when V is contained, in order to obtain the effect of adding V, the V content is preferably 0.005% or more, more preferably 0.008% or more, and even more preferably 0.010% or more.

[0022] (Ta:0.100% or less) Ta, like Ti and Nb, contributes to increasing the strength of steel sheets. In addition, Ta partially dissolves in Nb carbides and Nb carbonitrides to form composite precipitates such as (Nb, Ta)(C, N). This is thought to have the effect of significantly suppressing the coarsening of precipitates and stabilizing the contribution of precipitation strengthening to strength. For this reason, Ta may be added as necessary. However, even if Ta is contained in excess, the effect of stabilizing precipitates becomes saturated and the alloy cost increases, so the Ta content is preferably 0.100% or less, more preferably 0.080% or less, and further preferably 0.060% or less. On the other hand, when Ta is contained, in order to obtain the effect of adding Ta, the Ta amount is preferably 0.001% or more, more preferably 0.010% or more, and further preferably 0.020% or more.

[0023] (W:0.500% or less) W is effective for precipitation strengthening of steel and may be added as necessary. However, if the W content is too large, the area ratio of hard martensite becomes excessive, and during hole expansion testing, microvoids at the grain boundaries of martensite increase, and further, crack propagation progresses, and stretch flangeability may decrease. Therefore, the W content is preferably 0.500% or less, more preferably 0.400% or less, and even more preferably 0.300% or less. On the other hand, when W is contained, in order to obtain the effect of adding W, the W amount is preferably 0.001% or more, more preferably 0.010% or more, and even more preferably 0.020% or more.

[0024] (Cu:2.00% or less) Cu is an element that has the effect of suppressing the formation of pearlite during cooling after heating at a temperature T1 described later. However, if the amount of Cu is too large, the amount of hard martensite becomes excessive, and it may be difficult to obtain the required workability. Therefore, when Cu is contained, from the viewpoint of improving the workability, the amount of Cu is preferably 2.00% or less, more preferably 1.00% or less, and even more preferably 0.80% or less. On the other hand, when Cu is contained, in order to obtain the effect of adding Cu, the Cu amount is preferably 0.01% or more, more preferably 0.08% or more, and further preferably 0.10% or more.

[0025] (Ni: 1.00% or less) Ni is an element that stabilizes the retained austenite and is effective in ensuring better ductility. Furthermore, Ni is an element that increases the strength of the steel by solid solution strengthening. Therefore, Ni may be contained as necessary. However, if the Ni content is too large, the area ratio of hard martensite becomes excessive, and during a hole expansion test, microvoids at the grain boundaries of martensite increase, and further, crack propagation progresses, and hole expandability may decrease. Therefore, the Ni content is preferably 1.00% or less, more preferably 0.70% or less, and even more preferably 0.40% or less. On the other hand, when Ni is contained, in order to obtain the effect of adding Ni, the Ni amount is preferably 0.005% or more, more preferably 0.01% or more, and further preferably 0.10% or more.

[0026] (Sn: 0.200% or less, Sb: 0.200% or less) Sn and Sb may be added as necessary from the viewpoint of suppressing decarburization in a region of about several tens of μm in the surface layer of the steel sheet caused by nitriding or oxidation of the steel sheet surface, which prevents a decrease in the area ratio of martensite in the steel sheet surface and is effective in ensuring strength and material stability. However, excessive addition of Sn and Sb may result in a decrease in toughness, and therefore the Sn content and Sb content are each preferably 0.200% or less, more preferably 0.100% or less, and further preferably 0.050% or less. On the other hand, when Sn and Sb are contained, in order to obtain the effects of adding Sn and Sb, the Sn content and Sb content are each preferably 0.001% or more, and more preferably 0.002% or more.

[0027] (Cr:1.000% or less) Cr is an element that has the effect of suppressing the formation of pearlite during cooling after heating at a temperature T1 described later. However, if the Cr content is too large, the amount of hard martensite becomes excessive, and it may be difficult to obtain the required workability. Therefore, when Cr is contained, from the viewpoint of improving the workability, the Cr content is preferably 1.000% or less, more preferably 0.800% or less, and even more preferably 0.500% or less. On the other hand, when Cr is contained, in order to obtain the effect of adding Cr, the Cr amount is preferably 0.005% or more, more preferably 0.010% or more, and further preferably 0.015% or more.

[0028] (Mo: 1.000% or less) Mo is an element that has the effect of suppressing the formation of pearlite during cooling after heating at a temperature T1 described later. However, if the amount of Mo is too large, the amount of hard martensite becomes excessive, and it may be difficult to obtain the required workability. Therefore, when Mo is contained, from the viewpoint of improving the workability, the amount of Mo is preferably 1.000% or less, more preferably 0.800% or less, and even more preferably 0.500% or less. On the other hand, when Mo is contained, in order to obtain the effect of adding Mo, the Mo amount is preferably 0.005% or more, more preferably 0.010% or more, and further preferably 0.015% or more.

[0029] (B:0.0050% or less) B is an element useful for suppressing the formation and growth of polygonal ferrite from the austenite grain boundaries. However, if the B content is too high, the workability may be insufficient. Therefore, when B is contained, from the viewpoint of improving the workability, the B content is preferably 0.0050% or less, more preferably 0.0040% or less, and even more preferably 0.0030% or less. On the other hand, when B is contained, in order to obtain the effect of adding B, the B content is preferably 0.0003% or more, more preferably 0.0004% or more, and even more preferably 0.0005% or more.

[0030] (Mg:0.0050% or less) Mg is effective in improving the adverse effect of sulfides on hole expandability by spheroidizing the sulfides, and therefore Mg may be contained as necessary. However, if the Mg content is too high, the amount of inclusions increases, which may cause defects on the surface and inside of the steel sheet. Therefore, the Mg content is preferably 0.0050% or less, more preferably 0.0040% or less, and even more preferably 0.0030% or less. On the other hand, when Mg is contained, in order to obtain the effect of adding Mg, the Mg amount is preferably 0.0005% or more, and more preferably 0.0008% or more.

[0031] (Zr:0.100% or less) Zr is effective in improving the adverse effect of sulfides on hole expandability by making the sulfides spheroidal, and therefore Zr may be contained as necessary. However, if the Zr content is too high, the amount of inclusions increases, which may cause defects on the surface and inside of the steel sheet. Therefore, the Zr content is preferably 0.100% or less, more preferably 0.080% or less, and further preferably 0.060% or less. On the other hand, when Zr is contained, in order to obtain the effect of adding Zr, the Zr amount is preferably 0.0005% or more, more preferably 0.010% or more, and further preferably 0.020% or more.

[0032] (REM:0.0050% or less) REM (rare earth metal) is effective in improving the adverse effect of sulfides on hole expandability by making the sulfides spheroidal, and therefore REM may be contained as necessary. However, if the REM content is too high, the number of inclusions increases, which may cause defects on the surface and inside of the steel sheet. Therefore, the REM content is preferably 0.0050% or less, more preferably 0.0040% or less, and even more preferably 0.0030% or less. On the other hand, when REM is contained, in order to obtain the effect of adding REM, the REM amount is preferably 0.0003% or more, and more preferably 0.0005% or more.

[0033] (Ca:0.0050% or less) Ca is an effective element for improving workability by controlling the morphology of sulfides. However, if the Ca content is too high, it may adversely affect the cleanliness of the steel. Therefore, when Ca is contained, the Ca content is preferably 0.0050% or less, more preferably 0.0045% or less, and even more preferably 0.0040% or less. On the other hand, when Ca is contained, in order to obtain the effect of adding Ca, the Ca amount is preferably 0.0003% or more, more preferably 0.0005% or more, and even more preferably 0.0008% or more.

[0034] 《Remainder》 The balance of the composition is composed of Fe and unavoidable impurities.

[0035] <Hot rolling: Manufacturing of hot-rolled steel sheets> The steel slab having the above-mentioned composition is hot-rolled to obtain a hot-rolled steel sheet. The hot-rolling conditions are not particularly limited and may be in accordance with a conventional method, but the preferred conditions are as follows. First, a steel slab is heated to a temperature range of 1100° C. to 1300° C., and then hot rolling is completed in a temperature range of 870° C. to 950° C. In this manner, a hot-rolled steel sheet is obtained.

[0036] <Softening treatment for hot-rolled steel sheet> As described above, when a hot-rolled steel sheet is subjected to cold rolling (described later), the sheet passability may be insufficient (the hot-rolled steel sheet may crack or break, or the hot-rolled steel sheet may be too hard to be rolled). In hot-rolled steel sheets, carbides such as cementite are precipitated at the grain boundaries, and it is presumed that these carbides cause cracks and breakages in the hot-rolled steel sheets during cold rolling. In particular, high-Si steel with a high Si content is prone to embrittlement, and therefore tends to have poor sheet threadability. If a hot-rolled steel sheet in a cracked or broken state is cold-rolled, the rolls used for cold rolling may be damaged.

[0037] Therefore, in the present manufacturing method, the hot-rolled steel sheet is subjected to a softening treatment, which will be described later, before being subjected to cold rolling. Hot-rolled steel sheets that have been softened are less likely to crack or break during cold rolling and have excellent passability. This is presumably because the softening process causes the carbides that cause cracks to disappear or shrink.

[0038] The softening treatment is a treatment in which the hot-rolled steel sheet is heated at a treatment temperature Ta1 for a treatment time ta1. The treatment temperature Ta1 is a temperature not lower than Ta-50°C and not higher than Ta+50°C. The processing time ta1 is equal to or less than the time ta. Ta (unit: °C) and ta (unit: time) are calculated using the following formula. Ta=600-[Si%]×100 ta=10-[Si%]×4 In the above formula, [Si%] is the Si content (unit: mass%) in the above-mentioned component composition.

[0039] For the reason that the sheet passing property is more excellent, the treatment temperature Ta1 of the softening treatment is preferably Ta-30°C or more, more preferably Ta-20°C or more, and further preferably Ta-10°C or more. For the same reason, the treatment temperature Ta1 of the softening treatment is preferably Ta+30° C. or lower, more preferably Ta+20° C. or lower, and even more preferably Ta+10° C. or lower.

[0040] For the reason that the sheet passing property is more excellent, the treatment time ta1 of the softening treatment is preferably ta-0.5 hours or less, more preferably ta-1 hour or less, and further preferably ta-1.5 hours or less. On the other hand, the treatment time ta1 of the softening treatment is preferably 0.5 hours or more, more preferably 1 hour or more, and even more preferably 1.5 hours or more.

[0041] The atmosphere in which the softening treatment is carried out is, for example, a reducing atmosphere. An example of the reducing atmosphere is an atmosphere consisting of 10 to 30 volume % hydrogen gas and the remainder nitrogen gas. The softened hot-rolled steel sheet is then cooled, for example, to room temperature (23±5° C.) in order to be subjected to cold rolling. The softened hot-rolled steel sheet may be optionally subjected to pickling.

[0042] <Physical properties of softened hot-rolled steel sheet> (Charpy impact value) Charpy impact value (unit: J / cm 2 ) is the absorbed energy (unit: J) obtained by the Charpy impact test, multiplied by the cross-sectional area of ​​the test piece (unit: cm 2 ) is the value divided by

[0043] It can be said that a hot-rolled steel sheet with a high Charpy impact value is more likely to absorb impact energy and is less likely to be destroyed (less likely to crack or break during cold rolling). Therefore, the Charpy impact value can be an indicator of whether a hot-rolled steel sheet has excellent sheet passing properties during cold rolling. The Charpy impact value of softened hot-rolled steel sheet is 30 J / cm 2 More than 40 J / cm is preferable. 2 More preferably, 50 J / cm 2 More preferably, 60 J / cm 2 The above is particularly preferred.

[0044] The Charpy impact test is performed in accordance with JIS Z 2242:2018 "Charpy impact test method for metallic materials" (test temperature: 5°C, notch shape: V-notch, impact blade radius: 2 mm).

[0045] (Carbide diameter) As described above, in a hot-rolled steel sheet that has been subjected to a softening treatment, carbides are reduced in size. Therefore, the diameter of the carbides can also be an indicator of whether or not the hot-rolled steel sheet has excellent threadability during cold rolling. In the softened hot-rolled steel sheet, the diameter of the carbides is preferably 50 nm or less, more preferably 40 nm or less, and even more preferably 30 nm or less.

[0046] The diameter of the carbide is determined as follows. The hot-rolled steel sheet is polished to expose a cross section at 1 / 4 of the sheet thickness (a position corresponding to 1 / 4 of the sheet thickness in the depth direction from the surface of the hot-rolled steel sheet) as an observation surface. The observation surface is corroded with 3% by volume of nital, and then observed at a magnification of 10,000 times using a scanning electron microscope (SEM) to obtain an SEM image. In the SEM image, the diameter of the carbide (specifically, cementite, which is an iron carbide) is obtained. More specifically, the maximum and minimum lengths of each carbide are measured, and the sum of the two is divided by 2 ((maximum length + minimum length) / 2) and regarded as the diameter of the carbide. The average value of the diameters of 100 randomly selected carbides is calculated as the diameter (unit: nm) of the carbides in the hot-rolled steel sheet.

[0047] (Vickers hardness) It can be said that a hot-rolled steel sheet with a small Vickers hardness is easy to cold roll and has excellent passability. Specifically, the Vickers hardness of the softened hot-rolled steel sheet is preferably less than 380 HV, more preferably less than 370 HV, and even more preferably less than 360 HV.

[0048] The Vickers hardness of the hot-rolled steel sheet is determined in accordance with JIS Z 2244 with a test force F of 9.8N.

[0049] Cold rolling: Manufacturing of cold-rolled steel sheets Next, the softened hot-rolled steel sheet is subjected to cold rolling to obtain a cold-rolled steel sheet. As described above, the hot-rolled steel sheet that has been subjected to the softening treatment has excellent sheet passing properties.

[0050] The cold rolling reduction is preferably 30% or more, which allows fine austenite to be generated during the heat treatment described below, ultimately resulting in fine retained austenite and martensite, which not only improves the balance between strength and ductility but also has the potential to improve stretch flangeability and bendability. On the other hand, the upper limit of the cold rolling reduction is not particularly limited, but from the viewpoint of the load applied in the cold rolling, it is preferably 85% or less, and more preferably 75% or less. In the present manufacturing method, since the hot-rolled steel sheet to be cold-rolled has been subjected to softening treatment, cold rolling can be performed at a high reduction ratio, and a thinner cold-rolled steel sheet can be obtained.

[0051] <Heat treatment for cold-rolled steel sheet> After cold rolling, the cold rolled steel sheet is subjected to a heat treatment. The technical significance of the heat treatment in the present invention is roughly as follows. Normally, high carbon and high manganese steels have high strength, but because they contain a large amount of alloying elements, the rate of bainite transformation is very slow and the transformation start line during isothermal holding shifts to the long-term side, which delays the bainite transformation and makes it difficult to utilize the retained austenite. Therefore, by utilizing the fact that the rate of bainite transformation becomes significantly faster when martensite and untransformed austenite coexist, heating, cooling, and cooling cessation are performed in a short period of time, and reheating is further repeated twice. That is, martensite nucleation by cooling promotes bainite transformation during reheating due to the swing-back effect, and once the bainite transformation has progressed, martensite nucleation occurs again by cooling. This allows the bainite transformation to be fully utilized in a short time during the second reheating, and ensures high ductility by securing retained austenite, which contributes to improved ductility. At the same time, by preventing the formation of martensite, good stretch flangeability can be achieved. If reheating is not performed or if reheating is performed only once, the proportion of martensite with a large aspect ratio increases, and ductility and stretch flangeability may become insufficient. Therefore, it is important to repeat reheating twice in order to obtain the desired structure and material properties.

[0052] Fig. 1 is a schematic diagram showing a temperature pattern of heat treatment after cold rolling. The heat treatment has the temperature pattern (thermal history) shown in Fig. 1. A more detailed description will be given below.

[0053] {Heated at temperature T1 in the austenite single phase region for 15 seconds to 1000 seconds} First, the cold-rolled steel sheet is heated at a temperature T1 in the austenite single phase region for 15 seconds to 1000 seconds. The high-strength steel plate obtained by this manufacturing method has a structure mainly consisting of tempered martensite and bainite obtained by transforming austenite. In order to secure the amount of tempered martensite and bainite in the steel plate and to increase the strength of the steel plate, it is preferable that the amount of ferrite is as small as possible. For this reason, heating (annealing) at a temperature T1 in the austenite single phase region is necessary. The temperature T1 is preferably Ac3 (austenite transformation point) or higher, and more preferably (Ac3 + 15°C) or higher.

[0054] Ac3 (unit: °C) is calculated using the following formula. Ac3=937.2-436.5×[C%]+56×[Si%]-19.7×[Mn%]-4.9×[Cr%]-16.3×[Cu%]+38 .1×[Mo%]+124.8×[V%]+136.3×[Ti%]-19.1×[Nb%]+198.4×[Al%]+3315×[B%] In the above formula, [X%] is the content (unit: mass%) of component X in the above-mentioned composition. [X%] of component X that is not contained is set to 0.

[0055] The temperature T1 is not particularly limited as long as it is in the austenite single phase region, but if it is too high, the growth of austenite grains becomes significant. This increases the area ratio of tempered martensite, increases the proportion of martensite with a large aspect ratio, decreases the area ratio of retained austenite, and may result in insufficient ductility and stretch flangeability. For this reason, the temperature T1 is preferably 1000°C or less, more preferably 950°C or less.

[0056] If the temperature T1 is below the austenite single phase region or the heating time at temperature T1 is too short, the reverse transformation to austenite does not proceed sufficiently during heating at temperature T1, the area ratio of ferrite increases, and it may become difficult to ensure strength. For this reason, the heating time at temperature T1 is 15 seconds or more, preferably 30 seconds or more, and more preferably 60 seconds or more.

[0057] On the other hand, if the heating time at temperature T1 is too long, the austenite will coarsen during heating, which will increase the area ratio of martensite, increase the proportion of martensite with a large aspect ratio, and decrease the area ratio of retained austenite, which may result in insufficient ductility and stretch flangeability. For this reason, the heating time at temperature T1 is 1000 seconds or less, preferably 800 seconds or less, and more preferably 600 seconds or less.

[0058] <Cooling to a temperature T2 between Ms-50℃ and Ms℃> The temperature T2 is important for achieving both strength and workability. The cold-rolled steel sheet heated at temperature T1 is cooled to temperature T2, which is the cooling stop temperature between Ms-50°C and Ms°C. By cooling to below Ms°C, a part of the austenite is transformed into martensite. The martensite generated during cooling to temperature T2 becomes the nucleus of bainite transformation during holding at temperature T3, which will be described later. It is important to promote bainite transformation during holding at temperature T3 and promote carbon concentration in the retained austenite.

[0059] If the temperature T2 is less than Ms-50°C, the amount of untransformed austenite that is transformed into martensite at the temperature T2 will be excessive, resulting in a large amount of tempered martensite and a small amount of retained austenite, making it impossible to achieve both excellent strength and workability. For this reason, the temperature T2 is Ms-50°C or higher. On the other hand, if the temperature T2 is equal to or higher than Ms°C, martensite cannot be secured at the time when cooling is stopped. This delays the bainite transformation during holding at the temperature T3, and ultimately makes it difficult to secure the desired amount of retained austenite. For this reason, the temperature T2 is set to be lower than Ms°C.

[0060] Ms (unit: °C) is calculated by the following formula. Ms=550-35×[Mn%]-13×[Si%]-10×[Cr%]-12×[Mo%]-600×{1-exp(-0.96×[C%])} In the above formula, [X%] is the content (unit: mass%) of component X in the above-mentioned composition. [X%] of component X that is not contained is set to 0.

[0061] {Heate to a temperature T3 of 500°C or less and hold for 15 seconds or more and 1000 seconds or less} The cold-rolled steel sheet cooled to temperature T2 is heated to a temperature T3 of 500° C. or less, and is held at temperature T3 for a period of 15 seconds to 1000 seconds. Holding at temperature T3 tempers the martensite formed by cooling from temperature T1 to temperature T2, transforms the untransformed austenite into bainite, and concentrates the solute C in the austenite. These steps promote the stabilization of austenite.

[0062] If the temperature T3 is too high, the bainite transformation is suppressed, making it difficult to ensure a desired amount of retained austenite. Therefore, the temperature T3 is 500°C or less, and preferably 420°C or less. On the other hand, if the temperature T3 is too low, the diffusion rate of solute C decreases, and the amount of C concentrated in austenite decreases, making it difficult to obtain the required C concentration in the retained austenite. Therefore, the temperature T3 is preferably 250°C or higher, more preferably 280°C or higher, and even more preferably 300°C or higher.

[0063] If the holding time at temperature T3 is too short, the bainite transformation is insufficient and the desired microstructure is not obtained. As a result, the workability may be insufficient. Therefore, the holding time at temperature T3 is 15 seconds or more, preferably 50 seconds or more, and more preferably 100 seconds or more.

[0064] The holding time at temperature T3 is sufficient if it is 1000 seconds due to the promotion effect of the bainite transformation caused by the martensite formed at temperature T2. If the holding time at temperature T3 is too long, stable retained austenite cannot be obtained as the final microstructure, and as a result, the desired ductility may not be obtained. Therefore, the holding time at temperature T3 is 1000 seconds or less, preferably 700 seconds or less, and more preferably 600 seconds or less.

[0065] <<Cooling to temperature T4, which is equal to or higher than Ms-200°C and lower than temperature T2>> When the holding at temperature T3 is completed, martensite, which serves as the nucleus of bainite transformation, is regenerated from the austenite that has not been transformed into bainite. For this reason, the cold-rolled steel sheet is cooled to temperature T4, which is the cooling stop temperature lower than temperature T2 described above. If the temperature T4 is equal to or higher than the temperature T2, the bainite transformation becomes insufficient after the steel is heated to and held at a temperature T5 described below, and the retained austenite that contributes to improving ductility is not obtained. For this reason, the temperature T4 is lower than the temperature T2. On the other hand, if the temperature T4 is less than Ms-200°C, the amount of martensite generated when cooling is stopped at the temperature T4 becomes excessive, and the amount of tempered martensite after heating to the temperature T5 becomes excessive, resulting in a decrease in the amount of retained austenite. As a result, it is not possible to achieve both excellent strength and workability. For this reason, the temperature T4 is Ms-200°C or higher.

[0066] {Heate to a temperature of 500℃ or less (T5) and hold for 15 to 1000 seconds} The cold-rolled steel sheet cooled to temperature T4 is heated again to a temperature T5 of 500° C. or less, and is held at temperature T5 for a period of 15 seconds to 1000 seconds. Holding at temperature T5 tempers the martensite formed by cooling from temperature T3 to temperature T4, and also transforms the untransformed austenite into bainite. Thus, at the stage where holding at temperature T5 is completed, a larger amount of solute C can be concentrated in the austenite than after holding at temperature T3, stabilizing the austenite and ultimately ensuring the retained austenite that contributes to improving ductility.

[0067] If the temperature T5 is too high, the bainite transformation is suppressed and the amount of retained austenite is reduced, so that the temperature T5 is 500°C or less, and preferably 420°C or less. On the other hand, if the temperature T5 is too low, the diffusion rate of solute C decreases, and the amount of C concentrated in austenite decreases, making it difficult to obtain the required C concentration in the retained austenite. Therefore, the temperature T5 is preferably 250°C or higher, more preferably 280°C or higher, and even more preferably 300°C or higher.

[0068] If the holding time at temperature T5 is too short, the bainite transformation is insufficient and the desired microstructure cannot be obtained. As a result, the workability may be insufficient. Therefore, the holding time at temperature T5 is 15 seconds or more, preferably 50 seconds or more, and more preferably 100 seconds or more.

[0069] The holding time at temperature T5 is sufficient if it is 1000 seconds due to the promotion effect of the bainite transformation caused by the martensite formed at temperature T4. If the holding time at temperature T5 is too long, stable retained austenite cannot be obtained as the final microstructure, and as a result, one or both of the desired strength and ductility may not be obtained. Therefore, the holding time at temperature T5 is 1000 seconds or less, preferably 700 seconds or less, and more preferably 600 seconds or less.

[0070] Other conditions As for other conditions, the heating rate and cooling rate are, for example, as follows. The cold-rolled steel sheet after cold rolling is heated, for example, from room temperature to a temperature T1. The heating rate to the temperature T1 is preferably 0.1° C. / sec or more, more preferably 0.5° C. / sec or more, while it is preferably 40° C. / sec or less, more preferably 30° C. / sec or less.

[0071] The cooling rate from temperature T1 to temperature T2 is preferably 5° C. / sec or more, more preferably 10° C. / sec or more, while it is preferably 50° C. / sec or less, more preferably 40° C. / sec or less.

[0072] The rate of temperature rise from temperature T2 to temperature T3 is preferably 5° C. / sec or more, more preferably 10° C. / sec or more, while it is preferably 100° C. / sec or less, more preferably 50° C. / sec or less.

[0073] The cooling rate from temperature T3 to temperature T4 is preferably 5° C. / sec or more, more preferably 10° C. / sec or more, while it is preferably 50° C. / sec or less, more preferably 40° C. / sec or less.

[0074] The rate of temperature rise from temperature T4 to temperature T5 is preferably 5° C. / sec or more, more preferably 10° C. / sec or more, while it is preferably 100° C. / sec or less, more preferably 50° C. / sec or less.

[0075] After being held at temperature T5, the cold-rolled steel sheet is cooled, for example, to room temperature. Suitable cooling methods include, for example, air cooling, gas cooling, furnace cooling, and water cooling. At this time, the cooling rate from temperature T5 is preferably 5°C / sec or more, more preferably 10°C / sec or more. On the other hand, it is preferably 1000°C / sec or less, more preferably 100°C / sec or less.

[0076] In the heat treatment described above, the holding temperature does not have to be constant as long as it is within the above-mentioned temperature range, and may vary within the above-mentioned temperature range. As long as the above-mentioned thermal history is satisfied, the heat treatment may be carried out in any facility. The surface of the heat-treated cold-rolled steel sheet may be subjected to temper rolling for shape correction. The heat-treated cold-rolled steel sheet may be subjected to a plating treatment to produce a hot-dip galvanized steel sheet, and further subjected to an alloying treatment to produce a hot-dip galvanized steel sheet.

[0077] [High strength steel plate] Next, the high-strength steel plate obtained by the present production method described above (hereinafter, also referred to as the present high-strength steel plate) will be described. The high strength steel sheet of the present invention is a so-called cold rolled steel sheet, and has the above-mentioned composition and the microstructure described below. The sheet thickness is not particularly limited, and is, for example, 5.0 mm or less. High strength means a tensile strength (TS) of 1300 MPa or more.

[0078] <Microstructure> Next, the microstructure (steel sheet structure) of the present high strength steel sheet will be described. In the following, the area ratio is the area ratio to the entire microstructure. The area ratio of each structure is determined by the method described in the examples below.

[0079] Ferrite area ratio: 0% to 10% Ferrite is a soft structure and contributes to ductility. However, if there is too much ferrite, it becomes difficult to achieve the desired tensile strength. Furthermore, during processing, strain is concentrated in the soft ferrite mixed in the hard structure, which easily generates cracks, resulting in failure to obtain the desired processability. If the amount of ferrite is small, a small amount of ferrite is isolated and dispersed in the hard structure, which can suppress the concentration of strain and prevent deterioration of workability. Therefore, the area ratio of ferrite is 10% or less, preferably 7% or less, and more preferably 5% or less. The area ratio of ferrite may be 0%, but from the viewpoint of ensuring workability, it may be, for example, 1% or more, and preferably 2% or more.

[0080] {Area ratio of tempered martensite: 40% or more and less than 80%} Tempered martensite contributes to improving strength, and therefore the area ratio of tempered martensite is 40% or more, preferably 45% or more, and more preferably 50% or more. On the other hand, if the tempered martensite is too much, as described below, the desired amount of retained austenite cannot be secured, and workability such as ductility becomes insufficient. Therefore, the area ratio of tempered martensite is less than 80%, preferably less than 75%, and more preferably less than 70%.

[0081] Martensite can be distinguished by observing the structure. Untempered martensite (as-quenched martensite) does not contain carbides in the structure. On the other hand, tempered martensite has carbides with random growth directions in the structure.

[0082] {Area ratio of bainite: 5% or more and less than 20%} Sufficient promotion of the bainite transformation is necessary to concentrate C in the untransformed austenite and obtain retained austenite. In addition, in order to obtain a desired tensile strength, the area fraction of bainite is 5% or more, preferably 6% or more, and more preferably 8% or more. On the other hand, if the amount of bainite is too large, the amount of retained austenite will be insufficient, and therefore the area ratio of bainite is less than 20%, preferably less than 18%, and more preferably less than 15%.

[0083] {Area ratio of martensite: 0% to 10%} Martensite is a hard structure and increases the strength of the steel plate. On the other hand, if the martensite content is too high, the amount of bainite decreases, a stable amount of retained austenite cannot be secured, and ductility decreases. In addition, martensite becomes the starting point of voids, which reduces stretch flangeability. Therefore, the area ratio of martensite is 10% or less, preferably 8% or less, and more preferably 6% or less. The area ratio of martensite may be 0%.

[0084] {Area ratio of retained austenite: 10% to 20%} During processing, the retained austenite transforms into martensite due to the TRIP (Transformation Induced Plasticity) effect, and the high carbon content of the hard martensite increases strength, while increasing strain dispersion and improving ductility. The coexistence of this type of retained austenite with bainite and martensite provides good workability even in the high-strength region with a tensile strength (TS) of 1,300 MPa or more. Specifically, the TS × El value can be set to 18,000 MPa·% or more, and the TS × λ value can be set to 40,000 MPa·%, achieving an extremely good balance between strength and workability. If the amount of retained austenite is too small, a sufficient TRIP effect cannot be obtained, and therefore the area ratio of the retained austenite is 10% or more, preferably 11% or more, and more preferably 12% or more. On the other hand, if the amount of retained austenite is too large, the hard martensite formed after the TRIP effect is exerted becomes excessive, and the toughness and stretch flangeability deteriorate. Therefore, the area ratio of the retained austenite is 20% or less, preferably 19% or less, and more preferably 18% or less.

[0085] 《Ratio (a / b): 0.5 or less》 If the ratio (a / b) of the area fraction (a) of martensite with an aspect ratio of less than 2.0 to the area fraction (b) of total martensite is too large, sufficient ductility and stretch flangeability may not be obtained. This is because if a large amount of martensite, which is extremely hard, has low deformability and poor toughness, with an aspect ratio of less than 2.0 (i.e., blocky), is present, the material cannot deform uniformly when strain is applied, and as a result, excellent ductility and stretch flangeability may not be obtained. For this reason, the ratio (a / b) is preferably equal to or less than 0.5, and more preferably equal to or less than 0.4. EXAMPLES

[0086] The present invention will be specifically described below with reference to examples, although the present invention is not limited to the examples described below.

[0087] <Hot rolling: Manufacturing of hot-rolled steel sheets> Steel slabs having the composition shown in Table 1 below (the balance being Fe and unavoidable impurities) were heated to 1250°C and then finish hot-rolled at 870°C to obtain hot-rolled steel sheets.

[0088] [Table 1]

[0089] <Softening treatment for hot-rolled steel sheet> The obtained hot-rolled steel sheets were subjected to softening treatment in a reducing atmosphere (hydrogen gas: 20 volume %, nitrogen gas: 80 volume %) under the conditions (treatment temperature Ta1 and treatment time ta1) shown in the following Table 2. When softening treatment was not performed, "-" is entered.

[0090] After that, the diameter of the carbides (unit: nm) and the Charpy impact value (unit: J / cm 2 ) and Vickers hardness (unit: HV) were measured. The results are shown in Table 2 below (underlined values ​​indicate values ​​outside the range or preferred range of the present invention). From a practical standpoint, the Charpy impact value is 30 J / cm 2 The Vickers hardness is preferably less than 380 HV.

[0091] [Table 2]

[0092] As shown in Table 2 above, the hot-rolled steel sheets Nos. 1 to 4, 9 to 10, and 13 to 14, in which the softening treatment temperature Ta1 is Ta-50°C or more and Ta+50°C or less, and the softening treatment time ta1 is ta hours or less, have carbides with a diameter of 50 nm or less and a Charpy impact value of 30 J / cm 2 That was all.

[0093] In contrast, the hot-rolled steel sheets Nos. 5 to 7, 11, and 15, in which the softening treatment temperature Ta1 is outside the range of Ta-50°C or more and Ta+50°C or less, and / or the softening treatment time ta1 is longer than ta hours, have carbide diameters exceeding 50 nm and Charpy impact values ​​of 30 J / cm 2 It was less than. Moreover, the hot-rolled steel sheets Nos. 8, 12 and 16, which were not subjected to softening treatment, had a Vickers hardness of 380 HV or more.

[0094] Cold rolling: Manufacturing of cold-rolled steel sheets Next, the hot-rolled steel sheets (excluding the hot-rolled steel sheets Nos. 8, 12 and 16 which were not subjected to softening treatment) were cold-rolled at a rolling reduction of 75% to obtain cold-rolled steel sheets having a thickness of 0.6 mm. At this time, the Charpy impact value is 30 J / cm 2 As for the cold-rolled steel sheets (Nos. 5 to 7, 11 and 15) obtained by cold rolling the hot-rolled steel sheets having a rolling speed of less than 1000 sq. m, cracks or breaks were found in some of them.

[0095] The hot-rolled steel sheets Nos. 8, 12 and 16, which were not subjected to softening treatment, could not be cold-rolled at a reduction ratio of 75% under the same conditions as the other hot-rolled steel sheets which had been subjected to softening treatment. For this reason, cold rolling was performed at a rolling reduction rate of 50% to obtain a cold-rolled steel sheet having a thickness of 1.2 mm.

[0096] <Heat treatment for cold-rolled steel sheet> Next, the obtained cold-rolled steel sheet was subjected to heat treatment according to the temperature pattern shown in FIG. 1 under the conditions shown in Table 3 below, and further subjected to temper rolling with a rolling reduction of 0.1% to obtain a high-strength steel sheet. Other conditions for the heat treatment of the temperature pattern shown in FIG. 1 were that the heating rate from room temperature to temperature T1 was 2° C. / sec., the cooling rate from temperature T1 to temperature T2 was 20° C. / sec., the heating rate from temperature T2 to temperature T3 was 30° C. / sec., the cooling rate from temperature T3 to temperature T4 was 15° C. / sec., the heating rate from temperature T4 to temperature T5 was 20° C. / sec., and the cooling rate from temperature T5 to room temperature was 15° C. / sec.

[0097] [Table 3]

[0098] <High strength steel plate> The area ratio of each structure in the obtained high-strength steel plate and the ratio (a / b) of the area ratio (a) of martensite having an aspect ratio of less than 2.0 to the area ratio (b) of total martensite were determined by the method described in paragraphs

[0082] to

[0087] of Patent Document 1. The results are shown in Table 4 below.

[0099] Furthermore, the tensile strength (TS, unit: MPa), total elongation (El, unit: %) and hole expansion ratio (λ, unit: %) of the obtained high-strength steel sheet were determined by the method described in paragraph

[0088] of Patent Document 1. Then, the product (TS×El) of the tensile strength (TS) and the total elongation (El), and the product (TS×λ) of the tensile strength (TS) and the hole expansion ratio (λ) were calculated. The results are shown in Table 4 below. When TS × El ≥ 18,000 [MPa·%], the material was evaluated as having excellent workability. When TS × λ ≧ 40,000 [MPa·%], the material was evaluated as having excellent workability.

[0100] [Table 4]

[0101] As shown in Table 4 above, all of the high strength steel sheets had good workability.

Claims

1. In mass percent, C: 0.20% or more and 0.50% or less, Si: 0.5% or more and 2.5% or less, Mn: 2.5% or more and 5.0% or less, P: 0.100% or less, S: 0.0500% or less, Al: 0.01% or more and 0.50% or less, and N: 0.010% or less; A hot-rolled steel sheet is obtained by hot-rolling a steel slab having a composition with the balance being Fe and unavoidable impurities, The hot-rolled steel sheet is subjected to a softening treatment at a treatment temperature Ta1 of Ta-50°C or more and Ta+50°C or less for a treatment time ta1 of ta or less, The hot-rolled steel sheet that has been subjected to the softening treatment is cold-rolled to obtain a cold-rolled steel sheet, The method for producing a high strength steel sheet includes heating the cold rolled steel sheet at a temperature T1 in the austenite single phase region for 15 seconds or more and 1000 seconds or less, then cooling to a temperature T2 of Ms-50°C or more and less than Ms°C, then raising the temperature to a temperature T3 of 500°C or less and holding the temperature therefor for 15 seconds or more and 1000 seconds or less, then cooling to a temperature T4 of Ms-200°C or more and less than the temperature T2, and then raising the temperature to a temperature T5 of 500°C or less and holding the temperature therefor for 15 seconds or more and 1000 seconds or less. When the content of component X in the composition is expressed in mass % as [X%], Ta, ta and Ms are calculated by the following formula in units of ° C., time and ° C., respectively. Ta=600-[Si%]×100 ta=10-[Si%]×4 Ms=550-35×[Mn%]-13×[Si%]-10×[Cr%]-12×[Mo%]-600×{1-exp(-0.96×[C%])}

2. The composition further comprises, in mass%, Ti: 0.100% or less, Nb: 0.100% or less, V: 0.100% or less, Ta: 0.100% or less, W: 0.500% or less, Cu: 2.00% or less, Ni: 1.00% or less, Sn: 0.200% or less, Sb: 0.200% or less, Cr: 1.000% or less, Mo: 1.000% or less, B: 0.0050% or less, Mg: 0.0050% or less, Zr: 0.100% or less, REM: 0.0050% or less; and The method for producing a high strength steel plate according to claim 1, further comprising the step of: adding at least one element selected from the group consisting of Ca: 0.0050% or less.

3. The method for producing a high strength steel sheet according to claim 1 or 2, wherein the softened hot-rolled steel sheet has carbides having a diameter of 50 nm or less.

Citation Information

Patent Citations

  • Method for producing high carbon hot rolled steel sheet

    JP2001200315A

  • High strength steel sheet and method for producing the same

    JP2021123801A

  • Manufacturing method for cold-rolled or galvanized dual-phase steel sheet with a strength of 980 MPa or more

    JP2021528562A

  • A pivoting angle measuring equipment of gyratory compactor

    KR1020210109297A

  • Automotive steel and a method for the fabrication of the same

    US20210054476A1